The novel host associations for the aphid parasitoid, Pauesia hazratbalensis (Hymenoptera: Braconidae: Aphidiinae). (2nd January 2020) - Heidari Latibari, Minoo; Moravej, Gholamhossein; Ghafouri Moghaddam, Mostafa; Barahoei, Hossein; Hanley, Guy A.
ABSTRACT: Here, we report a species of pine aphid, Cinara pinihabitans (Mordvilko, 1895) (Hemiptera, Lachnidae) as a new host record for Pauesia hazratbalensis Bhagat, 1981 (Hymenoptera, Braconidae, Aphidiinae), associated with Pinus mugo Turra (Pinaceae). The novel host, C. pinihabitans, was recently reported as an important pest of Iranian conifers in Razavi Khorasan Province. Thus, the present paper provides the first new host associations of P. hazratbalensis in a world background.